Peningkatan Produktivitas Tanaman Padi Melalui Aplikasi Bakteri Pgpr (Plant Growth Promtion Rhizobacteria) - Harefa, Oferlina; Lase, Natalia Kristiani (Jurnal Ilmu Pertanian dan Perikanan, 2024)
One of the main food commodities in the world, including Indonesia, rice requires continuous efforts to increase productivity. The use of plant growth-promoting rhizobacteria (PGPR), which are microorganisms that function to enhance plant growth through various biological mechanisms, is one approach that is increasingly receiving attention. PGPR can accelerate flowering, increase resistance to abiotic stresses such as drought and salinity, and aid nutrient uptake, especially nitrogen and phosphorus. In addition, PGPR can reduce dependence on pesticides and chemical fertilizers and support more environmentally friendly agricultural practices. Recent studies have shown that the use of PGPR in marginal lands can increase crop yields, improve root structure, and increase water use effectiveness. In addition, the use of PGPR and seed coatings can improve germination and early plant growth. PGPR offers a sustainable solution for national food security as it has great potential to be applied to non-ideal lands such as saline soils. However, there are still problems to apply, mainly due to the growing bacterial population and varying environmental conditions. Therefore, additional research is needed to create ideal PGPR formulations and application methods to support sustainable agriculture in Indonesia.